Caracterização mecânica do alumínio reciclado como fundido - Oliveira, Ismael Noronha de (Universidade Federal Rural do Semi-Árido, 2019)
"The presente paper presents the study and mechanical characterization of recycled aluminum as a melt from beverage cans.The cans were selected and melted using an oven at ambient pressure.For the mechanical characterization, a Brinell hardness test was performed on 9 specimens and a tensile strength test for 9 specimens.Autodesk Inventor 2015 threedimensional modeling software was designed as the test specimen model for the tensile test of metallic materials defined in NBR ISO 6892: 2013.The tensile strength test was performed at room temperature with a speed of 20 mm / min and a load of 300 kN was applied.It was observed that the limits of tensile strength, yield limit and Brinell hardness determined were similar to that of a 3XXX series aluminum alloy.he modulus of elasticity was lower than that found in pure aluminum alloy. The impurities generated in the casting process may have influenced the results obtained
Monografia
Keywords: Fundição; Caracterização; Mecânica; Tração; Dureza; ENGENHARIAS::ENGENHARIA MECANICA